Brain Marker Links Stress and Nicotine Abstinence. Issue 6 (22nd May 2019) - Allenby, Cheyenne; Falcone, Mary; Ashare, Rebecca L; Cao, Wen; Bernardo, Leah; Wileyto, E Paul; Pruessner, Jens; Loughead, James; Lerman, Caryn
Abstract: Background: Subjective stress is a well-documented predictor of early smoking relapse, yet our understanding of stress and tobacco use is limited by reliance on self-reported measures of stress. We utilized a validated functional neuroimaging paradigm to examine whether stress exposure during early abstinence alters objective measures of brain function. Methods: Seventy-five participants underwent blood oxygen level dependent (BOLD) functional magnetic resonance imaging (fMRI) during the Montreal Imaging Stress Task (MIST) on two occasions: once during smoking satiety and once following biochemically confirmed 24-hour abstinence (order counterbalanced). The primary outcome measure was brain response during stress (vs. control) blocks of the MIST, assessed using whole-brain analysis corrected for multiple comparisons using clusters determined by Z ≥ 3.1. Results: Abstinence (vs. satiety) was associated with significantly increased activation in the left inferior frontal gyrus, a brain region associated with inhibitory control. Abstinence-induced change in brain response to stress was positively associated with change in self-reported stress. Conclusions: This study provides objective evidence that the brain response to stress is altered during the first 24 hours of a quit attempt compared to smoking satiety. Implications: These results point to the potential value of inoculating smokers with stress management training prior to a quit attempt.